PEMBUATAN ALAT PENGERING BERPUTAR (ROTARY) KOPI DAN LADA HITAM MENGGUNAKAN MIKROKONTROLER ARDUINO UNO DESA AIR RAMAN KABUPATEN KEPAHIANG PROPINSI BENGKULU - Anizar Indriani; Yovan Witanto; Hendra Hendra (DHARMA RAFLESIA, 2019)
Bengkulu Province has many potentials such as beaches, conservation forests, plantations and others. Plantations in Bengkulu consist of smallholders and private / BUMN businesses. Smallholder plantations include coffee, black pepper, palm, rubber, areca nut and other gardens. The results of this plantation are still traditionally processed, which is drying and drying in the open with the help of solar heat. This drying process is still being implemented where the quality is poorly controlled. This has caused the yield of the plantation in Bengkulu to be unknown to other regions. like coffee in the Bengkulu area which has a distinctive taste characteristic compared to other regions. Coffee that is processed is Robusta or Arabica coffee which is the mainstay of the people of Air Raman Village, Bengkulu Province. The processing process is dried in the yard of the house, field, roadside and others. This drying and processing process is easily polluted from dust, animal waste, uneven drying. And the erratic drying time causes the villagers to need a machine or garden processing technology. One technology is a rotary dryer. Rotary drying machines can be used by utilizing regional potential such as solar energy, wind energy, water energy and others. In addition to Coffee, this village also has garden products such as black pepper, Pinang and others where the process is the same as the coffee harvest. The advantage of this dryer is a shorter drying time, the use of solar energy can minimize operational costs for drying coffee and black pepper. The dried coffee and black pepper are free from animal waste, dust and various other types of garbage and the process of drying more than 4 days from drying is done manually / in the public yard. This is because the temperature inside the drying machine is rotary higher than the open air, the level of dryness of coffee and black pepper is produced evenly, because the temperature in the rotary dryer is equipped with a stirrer evenly spread so that the stirring process is no longer necessary. . The working mechanism of this tool is expected to help people producing coffee and black pepper to dry their crops so that the quality of coffee and black pepper is good and the selling value is high. The output of PPM activities The application of science and technology is a high selling value that will increase people's income, improve people's welfare to be better and also create new jobs for the community as a producer of rotary drying machines. The availability of appropriate technology for the design and construction of rotary drying machines. Scientific publications at the national level are published in the national journal Dharma Raflesia December 2018